Dose escalation via brachytherapy boost for nasopharyngeal carcinoma in the era of intensity-modulated radiation therapy and combined chemotherapy. (7th July 2017) - Chao, Hsing-Lung; Liu, Shao-Cheng; Tsao, Chih-Cheng; Lin, Kuen-Tze; Lee, Steve P; Lo, Cheng-Hsiang; Huang, Wen-Yen; Liu, Ming-Yueh; Jen, Yee-Min; Lin, Chun-Shu
ABSTRACT: To investigate if dose escalation using intracavitary brachytherapy (ICBT) improves local control for nasopharyngeal carcinoma (NPC) in the era of intensity-modulated radiation therapy (IMRT) and concurrent chemoradiation treatment (CCRT). We retrospectively analyzed 232 patients with Stage T1–3 N0–3 M0 NPC who underwent definitive IMRT with or without additional ICBT boost between 2002 and 2013. For most of the 124 patients who had ICBT boost, the additional brachytherapy was given as 6 Gy in 2 fractions completed within 1 week after IMRT of 70 Gy. CCRT with or without adjuvant chemotherapy was used for 176 patients, including 88 with and 88 without ICBT boost, respectively. The mean follow-up time was 63.1 months. The 5-year overall survival and local control rates were 81.5% and 91.5%, respectively. ICBT was not associated with local control prediction ( P  = 0.228). However, in a subgroup analysis, 75 T1 patients with ICBT boost had significantly better local control than the other 71 T1 patients without ICBT boost (98.1% vs 85.9%, P  = 0.020), despite having fewer patients who had undergone chemotherapy (60.0% vs 76.1%, P  = 0.038). Multivariate analysis showed that both ICBT ( P  = 0.029) and chemotherapy ( P  = 0.047) influenced local control for T1 patients. Our study demonstrated that dose escalation with ICBT can improve local control of the primary tumor for NPC patients with T1 disease treated with IMRT, even without chemotherapy.